The Metropolitan Century Understanding urbanisation and its consequences (OCDE, 2015)
By the end of this "Metropolitan Century", most of the urbanisation on our planet islikely to be completed. The urban population will have increased from less than 1 billionin 1950 to roughly 6 billion by 2050. By 2100, it is likely to reach somewhere around9 billion, corresponding to close to 85% of the projected total population.The first truly big wave of urbanisation got underway in the 18th century when theemergence of manufacturing industry created an unprecedented demand for labour inspecific locations. Cities of several hundred thousand people emerged quickly near coalmines and ports. From the second half of the 20th century onwards, urbanisation hasspread from developed countries to developing countries. During this (ongoing) secondwave of urbanisation, it has been proceeding at an unprecedented speed.